2018
DOI: 10.1007/s11524-018-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Enrollment among Prison Inmates in a Non-expansion State: Exploring Predisposing, Enabling, and Need Factors Related to Enrollment Pre-incarceration and Post-Release

Abstract: Prison inmates suffer from a heavy burden of physical and mental health problems and have considerable need for healthcare and coverage after prison release. The Affordable Care Act may have increased Medicaid access for some of those who need coverage in Medicaid expansion states, but inmates in non-expansion states still have high need for Medicaid coverage and face unique barriers to enrollment. We sought to explore barriers and facilitators to Medicaid enrollment among prison inmates in a non-expansion sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Other authors claimed that the model does not cover all factors of healthcare utilisation, such as psychosocial factors, 22 and would be less suitable for studies on HIV 89 or healthcare coverage. 93 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors claimed that the model does not cover all factors of healthcare utilisation, such as psychosocial factors, 22 and would be less suitable for studies on HIV 89 or healthcare coverage. 93 …”
Section: Resultsmentioning
confidence: 99%
“…Other authors claimed that the model does not cover all factors of healthcare utilisation, such as psychosocial factors, 22 and would be less suitable for studies on HIV 89 or healthcare coverage. 93 Not all critics proposed model modifications, but some of the identified limitations may lead to modifications of or additions to the BMHSU. Based on their findings, some authors (n=12) identified additional factors not covered by the model that impact healthcare utilisation, 23 39 54 90 or competing priorities 23 39 (table 2).…”
Section: Application Of the Different Versions Of The Andersen Modelmentioning
confidence: 99%
“…Yet as a Medicaid nonexpansion state, there are few options to continue health care for low-income people re-entering the community. Despite a prison-based program that facilitates Medicaid enrollment (based on nonexpansion eligibility criteria) to pay for community hospitalization during incarceration [25], some qualitative evidence suggests that there may be substantial barriers to retaining and continuing Medicaid enrollment postrelease [18]. And only a small proportion of those hospitalized in our study (<3%) were old enough to eligible for Medicare.…”
Section: Discussionmentioning
confidence: 79%
“…When incarcerated persons are released from prison and return to their communities, they often face an array of economic and social challenges [17]. Those returning citizens who have serious health conditions have the additional burden of accessing and paying for health care [4,18]dand lack of care can result in greater morbidity and mortality. In this study, we examined the postrelease mortality among people who had a community hospitalization during their imprisonment.…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting data exist, and some studies have shown no benefit of intensive management interventions over control groups on post-release outcomes, though these programs had very high linkage to care in the control arm and high recidivism rates, making post-release outcomes more challenging to interpret (MacGowan et al, 2015;Wohl et al, 2011Wohl et al, , 2017. The expansion of Medicaid is an important tool for improving care delivery for individuals leaving jail or prison (Guyer, Serafi, Bachrach, & Gould, 2019), though individuals released in states which have not expanded Medicaid, particularly low-income individuals, face additional barriers (Grodensky et al, 2018;Washington Post Editorial Board, 2019). Ending the Medicaid exclusion for people under correctional supervision would allow for continuous access to mental health and substance abuse treatment which is associated with lower rates of recidivism (Pew Charitable Trusts, 2011) and could impact healthcare utilization.…”
Section: Discussionmentioning
confidence: 99%